2021
DOI: 10.1186/s12889-021-10319-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of the Sudanese people towards COVID-19: an online survey

Abstract: Background The Novel Corona virus SARS-CoV-2 emerged to affect the human population in 2019 causing COVID-19 pandemic. The only preventive measures available are social distancing, hand washing and face masks. This study aims to assess the knowledge, attitude and practice of the Sudanese people towards COVID-19. Methods An online cross-sectional study targeting adult Sudanese people was conducted in April 2020. The study used a self-administered qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 12 publications
3
26
6
Order By: Relevance
“…This study indicated that students who were living in urban residence had 3-times greater odds of good practice level towards COVID-19 prevention and control measures compared to those who were living in rural residence during the pandemic. This finding is similar to studies conducted among Indonesian undergraduate students ( 42 ), Sudan ( 30 ), and Nepalese residents.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This study indicated that students who were living in urban residence had 3-times greater odds of good practice level towards COVID-19 prevention and control measures compared to those who were living in rural residence during the pandemic. This finding is similar to studies conducted among Indonesian undergraduate students ( 42 ), Sudan ( 30 ), and Nepalese residents.…”
Section: Resultssupporting
confidence: 89%
“…This study revealed that 65% [95% CI 60, 70.1%] of college students had a good level practice towards the prevention measures of COVID-19 pandemic. This finding is lower than a study done in Syria (73.8%) ( 31 ), Pakistan (80.5%) ( 36 ), Sudan (89.9%) ( 30 ), students in 10 universities in Shaanxi Province, China (87.9%) ( 40 ), and Uganda (85.3%) ( 41 ). However, this finding is higher than studies conducted in Bangladesh (55.1%) ( 17 ), and Pakistan (57.3%) ( 20 ).…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…This incorporated educator population size, which according to the statistics provided by the Ministry of Education, Culture, Sports, Science and Technology, numbers around 1 million [ 26 ] with a 95% confidence level, and a margin of error of 5%. From a previous study, we elected to collect 1,000 questionnaires to improve the study’s validity [ 22 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%